Effects of cyclosporin A on expression of IL-2 and IL-2 receptors in normal and multiple sclerosis patients. - Calder, V; Bellamy, A; Owen, S; Lewis, C; Rudge, P; Davison, A; Feldmann, M (1987)
The effects of the immunosuppressant Cyclosporin A (CsA) on T cell activation in vivo and in vitro were examined using the monoclonal antibody, anti-Tac, for interleukin 2 (IL-2) receptors and 3.9C2, for a peptide fragment of human IL-2. Peripheral blood lymphocytes (PBL) were stimulated with PHA in the presence of CsA. The expression of IL-2 receptors and production of IL-2 were reduced. PBL from CsA-treated MS patients had significantly lower proportions of Tac+ cells compared with untreated patients. This inhibition was not reflected in the CSF lymphocyte populations from CsA-treated patients and indicates the urgent need for an immunosuppressant drug which can enter the CNS in sufficient concentrations to inhibit local T cell activation.